Interpretation of the Qur'an : a comparative study of the methodologies of Abdolkarim Soroush and Mohammad Mojtahed Shabestari - Zarasi, Mohammad (International Institute of Malay World & Islamic Civilization, International Islamic University Malaysia, 2018)
This study compared Mohammad Mojtahed Shabestari and Abdolkarim Soroush's methodologies of understanding the Qur'an. The principles of hermeneutics borrowed and implemented by Shabestari and Soroush were evaluated and compared. It analyses their views on the methodology of understanding the Qur'an, the differences in their approaches and their conformity and otherwise of their views with the Islamic worldview. Based upon a qualitative content analysis of their approaches, the study exposed and compared Shabestari and Soroush views on selected significant issues based on their principles of hermeneutics. Moreover, Shabestari and Soroush's views about the quiddity of the Qur'an were identified and compared accordingly. The traditional methodologies and their relation with hermeneutics were examined. The study concludes that according to Shabestari and Soroush, understanding the Qur'an does not occur purely and without having presupposition. The study shows that contrary to main stream understanding of Islam, Shabestari and Soroush argue that the Qur'an is the words of Prophet Mohammad. While Shabestari did not discuss the nature of revelation, Soroush “dream revelation” theory explains the nature of revelation.